2002
DOI: 10.1016/s0002-9440(10)64491-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Imbalances in Pediatric Intracranial Ependymomas Define Clinically Relevant Groups

Abstract: The outcome of pediatric ependymomas is difficult to predict based on clinical and histological parameters. To address this issue, we have performed a comparative genomic hybridization screen of 42 primary and 11 recurrent pediatric ependymomas and correlated the genetic findings with clinical outcome. Three distinct genetic patterns were identified in the primary tumors and confirmed by hierarchical cluster analysis. The first group of structural tumors, showed few, mainly partial imbalances (n ‫؍‬ 19). A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
107
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 27 publications
14
107
1
4
Order By: Relevance
“…It is also possible that the number of deletions is underestimated by the FISH technique (eg, small deletions or relative RB deletions in an extensively polyploid tumor). However, our frequencies of 9p and 13q losses are similar to those previously reported using other techniques 11,14,24,[32][33][34] and there appears to be no clear suggestion of a prognostic association based on the available data thus far. Therefore, it is probable that genes other than p16 and RB may be targeted by the 9p and 13q deletions in ependymomas.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is also possible that the number of deletions is underestimated by the FISH technique (eg, small deletions or relative RB deletions in an extensively polyploid tumor). However, our frequencies of 9p and 13q losses are similar to those previously reported using other techniques 11,14,24,[32][33][34] and there appears to be no clear suggestion of a prognostic association based on the available data thus far. Therefore, it is probable that genes other than p16 and RB may be targeted by the 9p and 13q deletions in ependymomas.…”
Section: Discussionsupporting
confidence: 82%
“…11,21,24,[31][32][33][34] Based on the recent finding of CGH detectable losses in high-grade examples, it was suggested that the RB pathway may be specifically targeted in the process of tumor progression. 24 In contrast, our larger study similarly identified a subset of ependymomas with 9p or 13q deletions by FISH, but there were no obvious associations with tumor grade, location, patients age, recurrences, or death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased expression (more than twofold) was found concerning PRELP, EPHX1, FY, and HSPA6, all located on chromosomal arm 1q, which frequently showed copy number gains in ependymoma. 7 Correspondingly, genes from frequently deleted regions 7,8,11 were found weakly expressed (Ͻ0.5-fold), eg, COX7A2, COL10A1, and TCP1 from chromosome 6q; CNTFR, RAGA, TXN, AMBP, and HSPA5 from chromosome 9; TUBA2, PRDX2, and LCP1 from chromosome 13; and RANBP1, MCM5, EP300, G22P1, BZRP, and MAPK12 from chromosomal arm 22q. All 39 ependymomas analyzed in this study revealed a more than 10-fold expression of CLU, encoding for the glycoprotein clusterin (apolipoprotein J).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 30 to 50% of pediatric ependymomas display balanced comparative genomic hybridization profiles in comparison to only 10% in adults. 7,8,11 This finding suggests that the development of ependymomas at younger age is often independent of chromosomal instability. The recent histological ependymoma classification has thus far proven to be an unreliable predictor of clinical outcome and relationship between ependymoma grade and specific chromosomal aberrations is also controversial.…”
mentioning
confidence: 92%
See 1 more Smart Citation